Gambaran Kejadian Persalinan pada Ibu dengan Preeklampsia di RSUD Dr. Soeselo Slawi Kabupaten Tegal - Mutiarawati Mutiarawati; Reny Eka Saputri; Nora Rahmanindar (Universitas Muhamadiyah Manado, 2026)
Preeclampsia is one of the leading causes of maternal mortality and may result in various complications during pregnancy and childbirth. In Tegal Regency, preeclampsia contributed to 27% of maternal deaths in 2024; therefore, studies on childbirth characteristics among mothers with this condition are needed. This study aimed to identify the characteristics of childbirth events in mothers with preeclampsia at Dr. Soeselo Slawi Regional Hospital, Tegal Regency. A descriptive design with a retrospective approach was used by reviewing the medical records of 202 mothers who delivered with preeclampsia during 2025. Data were analyzed univariately and presented as frequency distributions and percentages. The results showed that most mothers underwent operative delivery (62.38%), while spontaneous and induced labor accounted for 37.13% and 0.50%, respectively. Most deliveries occurred at preterm gestational age (62.38%), followed by term (36.14%) and postterm (1.49%) deliveries. Maternal and obstetric complications included bleeding (6.93%), fetal distress (4.95%), eclampsia (1.49%), and HELLP syndrome (0.99%). Most neonates had normal birth weight (82.18%) and did not require NICU care (95.05%), although low birth weight (17.82%) and NICU admission (4.95%) were still identified. The maternal clinical condition was dominated by blood pressure of 140–159/90–109 mmHg (75.74%). Proteinuria was found in 46.53% of respondents, with moderate proteinuria (+2) as the predominant category (38.30%). In conclusion, childbirth among mothers with preeclampsia was dominated by operative and preterm deliveries. These findings emphasize the importance of early detection and optimal management of preeclampsia to reduce maternal and neonatal complications and improve the quality of maternal-infant health services overall.